Evaluation of the photoprotective and antioxidant potential of an avobenzone derivative - Pasuch Gluzezak, Ana Júlia; Dos Santos, Jean Leandro; Maria-Engler, Silvya Stuchi; Gaspar, Lorena Rigo (Frontiers in Physiology, 2024)
Solar radiation can cause damage to the skin and the use of sunscreens is one of the main protection measures. However, photounstable UV filters can generate photoproducts and reactive oxygen species (ROS). Adding antioxidants, such as resveratrol (RESV), to boost the action of UV filters in sunscreens is an interesting strategy for reducing the UV radiation exposure damage. Though, new compounds must have their stability, safety and efficacy guaranteed. Avobenzone (AVO), a commonly used UV filter, stands out as a great candidate for structural modification to enhance stability; its molecular hybridization with other UV filters and antioxidants can lead to safer and effective compounds. In this context, this study evaluated the photoprotective and antioxidant potential of an AVO's derivative, hybrid with RESV's molecule, using in vitro models of monolayer cells and reconstructed human skin (RHS). Phototoxic potential was evaluated using fibroblasts and the antioxidant activity was conducted using the DCFH2-DA probe in HaCaT keratinocytes and in house RHS. The derivative showed absorption in the UVB (280 -320 nm) range and photostability. It did not show phototoxic nor photoreactivity potential. It was also able to photo stabilize a photounstable combination of UV filters, AVO and octyl methoxycinnamate (OMC), and to reduce their phototoxic potential. Regarding the antioxidant activity, the derivative was able to protect against UVA-induced ROS production in the HaCaT keratinocytes model, being statistically equal to the antioxidant control, quercetin (10 μg/mL). The study performed in the RHS model showed a reduction of 30.7% of ROS generation, being statistically different from the irradiated control. This study showed that AVO's structure modifications can produce a broad spectrum, non-phototoxic, non-photoreactive and photostable derivative for sunscreen and anti-aging formulations, enhancing protection against oxidative stress induced by UV radiation, also improving sun protection effectiveness. In addition to the monolayer model, the use of a standardized in house RHS model brought relevance to evaluate the effects of UV radiation and skin aging, as it mimics human physiological conditions, and allows us to test new compounds and seek for protection mechanisms against such skin damage.